Knowledge by default. (19th November 2021) - Gordon, Robert M.
Abstract: The target article presents strong empirical evidence that knowledge is basic. However, it offers an unsatisfactory account of what makes knowledge basic. Some current ideas in cognitive neuroscience – predictive coding and analysis by synthesis – point to a more plausible account that better explains the evidence.